Green roof: an ecological soluction - Pereira, Érik Aparecido de Souza; Franzolin, Nataly; Feitoza, Jaquelline da Silva (Revista Hipótese, 2020)
The housing’s thermal behavior is na importante fator and the green roofs are potencial reducers of rainwater flow, being used in any roof. Through of prototype was evaluated thethermal reduction potential and rainwater flow of green roof. The monitoring results showed that the green roof brings positive thermal and drainage benefits.
Keywords: Green roof; Thermal comfort; Water flow; Civil construction